Preparation and characterization of selenium enriched-Bifidobacterium longum DD98, and its repairing effects on antibiotic-induced intestinal dysbacteriosis in mice. Issue 8 (25th July 2019) - Zhu, Hui; Zhou, Yan; Qi, Yan; Ji, Rui; Zhang, Junliang; Qian, Zhixiang; Wu, Chunzhen; Tan, Jun; Shao, Lei; Chen, Daijie
Abstract : The aim of this study was to investigate the characteristics of a novel selenium-enriched Bifidobacterium longum DD98 (Se- B. longum DD98) supplement food and its repairing effects on the intestinal ecology of mammals. Abstract : The aim of this study was to investigate the characteristics of a novel selenium-enriched Bifidobacterium longum DD98 (Se- B. longum DD98) supplement food and its repairing effects on the intestinal ecology of mammals. We assessed the growth, Se accumulation, and Se biotransformation of B. longum DD98 and its effects on antibiotic-induced intestinal dysbacteriosis in mice. The viable bacterial count at the end of fermentation was not significantly affected by the presence of Se. Bifidobacterium longum DD98 took up inorganic Se from the medium and biotransformed it into Se-containing proteins and selenoamino acids. The dominant Se species was selenomethionine (SeMet), which comprised 87% of the total Se in Se- B. longum DD98. Furthermore, Se- B. longum DD98 showed better regulation of the disrupted intestinal microbiota back to normal levels and repaired damaged colon tissues compared to the natural recovery and B. longum DD98 treatments. These findings suggest that B. longum DD98 efficiently biotransformed inorganic Se into more bioactive organic Se forms and may have therapeutic potential for the restoration of antibiotic-induced intestinal dysbacteriosis.